Effect of Filler Particle Size on the Recyclability of Fly Ash Filled HDPE Composites - Mohammed N. Alghamdi (Polymers, 2021)
Fly ash polymer composites are innovative high-performance materials that reduce the environmental worries and disposal complications of heavy industry produced fly ash. This study developed and characterized such composites of high-density polyethylene (HDPE) matrices and found that the use of small (50–90 µm) particles of fly ash could give rise to the tensile modulus (~95%) and tensile strength (~7%) of their reinforced composites when compared to neat HDPE materials. While these results themselves convey a strong message of how fly ash can be effectively utilized, this was not the key aim of the current study. The study was extended to examine the effect of fly ash particle size on the recyclability of relevant HDPE composites. The extrusion-based multiple recycling of composites gave slightly lower mechanical properties, primarily due to filler/matrix delamination when large fly ash particles were used. Compared to freshly made fly ash-filled HDPE composites, although using small (50–90 µm) fly ash particles reduced the tensile modulus and tensile strength of recycled composites, the values were still far above those from neat HDPE materials. This novel insight directs the effective utilization of fly ash and provides long-term sustainable and economical solutions for their practical applicability.